2006
DOI: 10.1007/s10764-005-9001-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Selection in the Loud Calls of Male Primates: Signal Content and Function

Abstract: Researchers have used sexual selection theory and hypotheses based on intersexual mate choice and intrasexual mate competition to explain the role of spontaneous long-distance vocalizations emitted by adult maleprimates, relying on the tacit assumption that assessment or identity cues are encoded in the vocalizations. I review the published literature and aim to substantiate a relationship between sexual selection and long-distance vocal communication in primates. First, I review findings from nonprimate taxa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 130 publications
(196 reference statements)
0
75
0
1
Order By: Relevance
“…Recent research has focused on the evolutionary reasons for the pubertal development of vocal sex differences in humans [11] and non-human primates [12]. Of particular interest has been sexual selection, which operates through both mate choice, favouring ornaments and sexual displays for attracting mates, and contest competition, favouring size, strength, aggression, weapons and threat displays [13].…”
Section: Sexual Selection and Human Voicesmentioning
confidence: 99%
“…Recent research has focused on the evolutionary reasons for the pubertal development of vocal sex differences in humans [11] and non-human primates [12]. Of particular interest has been sexual selection, which operates through both mate choice, favouring ornaments and sexual displays for attracting mates, and contest competition, favouring size, strength, aggression, weapons and threat displays [13].…”
Section: Sexual Selection and Human Voicesmentioning
confidence: 99%
“…Some have suggested that male vocalizations evolve to intimidate male competitors and/or attract mates [6,13]. For example, among orang-utans, lower-ranking males avoid long calls given by higher-ranking males [14], suggesting that acoustic cues convey threat potential to conspecifics.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, scant evidence exists to support a role for sexual selection in shaping F 0 and other vocal sexual dimorphisms across primates [6], and there are plausible alternative hypotheses: F 0 dimorphism may represent a byproduct of selection for greater male size or long-distance transmission of male calls [36], or reflect selection for sex identification. The latter two hypotheses predict relationships between habitat and F 0 dimorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Species with greater levels of precopulatory male-male competition and reduced levels of sperm competition have been shown to possess adaptations that enable them to produce exaggerated calls, suggesting that sexual selection plays a critical role in regulating vocal communication (Delgado, 2006;Charlton and Reby, 2016). Given this, air sacs are likely to be more common, and perhaps larger, in species under strong sexual selection.…”
Section: Sexual Selection and The Size Exaggeration Hypothesismentioning
confidence: 99%